Hospital Quality Reporting in the United States: Does Report Card Design and Incorporation of Patient Narrative Comments Affect Hospital Choice? - Emmert, Martin; Schlesinger, Mark (Health services research, 2017)
OBJECTIVE To explore the impact of hospital report card design and incorporation of patient narrative comments on consumers' choices of hospitals. DATA SOURCES Primary data collected from an online survey with 1,350 respondents in February, 2015. STUDY DESIGN A randomized 2 (narrative comments: yes, no) × 3 (design: representation of clinical performance in textual, star, numerical formats) between-subject online-based cross-sectional experiment. PRINCIPAL FINDINGS In 51 percent of all cases, respondents selected the hospital with the best clinical results. Report cards with a numerical design induced choices more focused on clinical ratings (56.0 percent chose the highest rated hospital) than those with textual information (48.1 percent) or star ratings (47.3 percent) (p < .001). Report cards without narrative comments (49.7 percent) and with narratives (51.4 percent) were not associated with significant difference in selecting top-rated clinical hospitals (p = .376). But there were significant interactions affecting choice of hospitals among exposure to narratives, formatting of clinical performance, and respondents' education. CONCLUSIONS Consumers have a difficult time synthesizing quality data in various formats. Hospital report cards continue to pose challenging choices, especially for those with limited education. Narrative comments in their earliest emerging forms do not seem to be altering hospital choice as much as the literature has suggested for other providers, but they may have consequential impact on the choices of certain subsets of consumers.